Relationship Between Musculoskeletal Load and Weight of Manual Fish Handling Via 2D Simulation - Kitagawa, Kodai (British Journal of Healthcare and Medical Research, 2022)
Fisherman experienced work-related musculoskeletal disorders (WMSDs) due to manual handling. Especially, manual handling for heavy fish makes physical load for fisherman. To prevent these WMSDs, fisherman should know the limit of weight in manual fish handling. Thus, the objective of this study was to find the relationship between the musculoskeletal load and weight of manual fish handling. This investigation was performed by the 2D musculoskeletal simulation. Posture of fishermen during manual fish handling on the commercial fishing boat was obtained from the Fishnet Open Images Database. Compression force of L5-S1 and joint torque of elbow, shoulder, knee, and ankle as musculoskeletal load were calculated by BlessPro2 software. The weight values of bigeye tuna, yellowfin tuna, and albacore tuna were used for this simulation. The results showed that compression force of L5-S1 and joint torque were increased with fish weight. In addition, the compression forces of L5-S1 during manual handling for bigeye tuna and yellowfin tuna were much larger than 3400 N as injury threshold of the National Institute of Occupational Safety and Health (NIOSH). These results indicate that fishermen should avoid heavy fish such as bigeye tuna and yellowfin tuna in manual fish handling for preventing WMSDs.